Life Skills Link to Mind Wandering Among University Students: An Exploratory Study - Kase, Takayoshi; Kawagoe, Toshikazu (Frontiers in Psychology, 2021)
The occurrence of mind wandering (MW) leads to lower performance on memory tasks related to lecture contents in educational settings, which has been recognized as problematic. To date, several dispositional factors have been reported as being associated with MW. This study investigated whether another psychological component—life skills—is linked to MW. Specifically, it clarified the relationship between life skills and two types of MW: state MW (occurs while performing a given task) and trait MW (occurs subjectively in daily life), using a sample of university students. From the perspective of cognitive and emotional control functions, life skills are thought to be related to the occurrence of MW. In addition to common questionnaire surveys, by recording and analyzing the participants’ self-reports for MW occurrence during the experimental task, we clarified not only the quantitative associations among the variables but also the qualitative differences. Multiple regression analysis for the data from 53 students showed that decision-making and coping-with-emotion skills are negatively related to the occurrence of mind wandering. The qualitative data additionally revealed that participants with high decision-making skills are more likely than those with low decision-making skills to attempt to maintain their concentration on the task by thinking about task execution. These results suggest that life skills are associated with MW and that the ability to inhibit MW may be enhanced by improving life skills because they comprise acquired, learnable behaviors and attitudes. Life skills training may help in reducing students’ MW in educational contexts.